A new species of Pupinidius Möllendorff, 1901 (Gastropoda, Stylommatophora, Enidae) from Jiuzhaigou, Sichuan, China - Zhong-Guang Chen; Yu-Ting Dai; Xiao-Ping Wu; Jiao Jiang; Shan Ouyang (Biodiversity Data Journal, 2024)
The genus Pupinidius Möllendorff, 1901 is endemic in China and Nepal and consists of 15 species. China is the distribution centre of it with 12 species being recorded.A new species, Pupinidius pulchellus Chen, Dai, Wu & Ouyang sp. nov. is described from Jiuzhaigou, Sichuan, China. It can be distinguished from congeneric species by the shell with wide and distinct radial stripes; the thin, slightly reflexed and reddish-brown peristome; the unpointed apex; the unfused A-1 and A-2; the sub-globular and well defined bursa copulatrix; the unexpanded diverticle and the presence of epiphallic caecum.